Ciliary body enlargement and cyst formation in uveitis. Issue 10 (October 1996) - Gentile, R C; Liebmann, J M; Tello, C; Stegman, Z; Weissman, S S; Ritch, R
Abstract : BACKGROUND: Acute anterior uveitis has diverse causes and systemic associations. Inflammation is predominantly localised to the iris and pars plicata. Little is known about the in vivo effects of uveitis on ciliary body anatomy. METHODS: Bilateral, high frequency, high resolution, ultrasound biomicroscopy was performed on consecutive patients with unilateral anterior uveitis to evaluate ciliary body anatomy. Imaging was repeated when possible during the clinical course. The cross sectional area of the anterior ciliary body was measured using image processing and analysis software. Measurements from the uveitic eyes were compared with the fellow eyes and the effect of treatment was evaluated. RESULTS: Fourteen patients were enrolled. Ultrasound biomicroscopy demonstrated a larger ciliary body cross sectional area in the uveitic eyes compared with the fellow, clinically uninvolved eyes (2.45 (SD 0.48) mm2 versus 1.55 (SD 0.15) mm2, (p = 0.0000; paired t test)). A ciliochoroidal effusion was present in one uveitic eye. Epithelial cysts were imaged bilaterally in four uveitic patients (29%) and unilaterally in unaffected eyes of two uveitic patients. Ciliary body cross sectional area decreased following steroid therapy (p = 0.0001; paired t test). New cysts were noted in three uveitic eyes during the follow up period and in none of the fellow, unaffected eyes. CONCLUSION: Ultrasound biomicroscopy offers a new approach to the evaluation of anterior uveitis. The response to treatment can be evaluated objectively and therapeutic efficacy can be more easily assessed. It has the potential to help elucidate the pathophysiology and anatomical changes of this heterogeneous group of disorders.